Орос, Англи, Монгол улс дахь хайкү шүлгийн эхлэл: The Start of Haiku in Russia, Britain and Mongolia - D., Budsuren (Mongolian Journal of Foreign Languages and Cultures, 2023)
Haiku have a simplicity that is deceptive both with regard to their depth of content and to their origins, and it is the aim of this and succeeding volumes to show that haiku require our purest and most profound spiritual appreciation, for they represent a whole world of religious and poetic experience. Poetry, culture, religion, are a manner of living, and this manner, like ordinary manners, is to a certain extent a matter of education, of thought and ideas, of habit and imitation. Every haiku, then, in so far as it is representative of a way of life, manner of living daily, is unwittingly didactic, teaches us above our will. We must note also that some poets have availed themselves of the haiku form to express thoughts and ideas of predominantly intellectual import.